PERBANDINGAN HUKUM PERIKANAN ANTARA INDONESIA DAN JEPANG MENGENAI ILLEGAL FISHING: Comparison of Fishery Laws between Indonesia and Japan Regarding Illegal Fishing - Ferdy Mahindra Azhary; Sri Untari Indah Artati (Faculty of Law, Universitas Trisakti, 2025)
Comparative law is an activity to study the legal systems that apply in various countries in order to find similarities and differences in structure, principles, and implementation. In Indonesia, provisions regarding fisheries are regulated through Law Number 45 of 2009 which is an amendment to Law Number 31 of 2004 concerning Fisheries, while in Japan fisheries law is regulated in the Japanese Fisheries Law. The formulation of the problem is what are the similarities and differences between fisheries law in Indonesia and Japan regarding illegal fishing and how to handle the problem of illegal fishing in Indonesia and Japan. This research is a normative legal research, descriptive type, using secondary data analyzed qualitatively, conclusions are drawn through deductive methods. The results of the discussion and conclusions are that there are differences and similarities in fisheries law between Indonesia and Japan regarding illegal fishing, namely similarities in terms of the existence of laws related to fisheries, the involvement of multi-sector law enforcement agencies, granting rights through official permits and commitment to international cooperation and there are also differences in fisheries law in Indonesia and Japan, namely the legal basis for fisheries, types of permits and licensing systems.